Perancangan UI/UX Sistem Manajemen Persuratan Menggunakan Metode Design Thinking - Fera, Fera Feriska Ristania Rahman; Angga Rustiawan; Dwi Ophi Ramadhan; Gugun Dermawan; Hendra Nelva Saputra; Alwas Muis (Jurnal PROCESSOR, 2025)
An efficient and digitized document management system is urgently needed in higher education administration to improve document management effectiveness. This study aims to design the user interface (UI) and user experience (UX) of a web-based document management system using the Design Thinking method. This method is used to understand user needs, design intuitive solutions, and develop interfaces that simplify interaction in document management. The design process includes the Empathize, Define, Ideate, Prototype, and Test stages. The results show that the generated UI/UX design improves ease of use and workflow efficiency, with a user satisfaction rate of 85%. The system's implementation has the potential to optimize digital correspondence, reduce administrative errors, and improve transparency. However, further development is needed to enhance accessibility, scalability, and integration with other administrative systems. This development will support a more efficient and transparent digital transformation in the operational processes of higher education institutions.